Staphylococcal carriage and antibodies to toxic shock syndrome toxin 1 in Brazilian women - De Magalhães Lopes, Carlos Alberto; Dias, Rogerio [UNESP]; Oliveira, Silvio Luis; Bergdoll, Merlin S. (My University, 1997)
A study of 215 women from different socioeconomic backgrounds in Botucatu, Brazil, was conducted to reveal possible clues why toxic shock syndrome (TSS) is seldom diagnosed in Brazil. Of the 215 women, 79 were colonized with Staphylococcus aureus either in the nasal passages and/or in the vaginal area, which is comparable to the colonization of individuals in the developed countries Thirteen of the women were colonized with S. aureus that produced toxic shock syndrome toxin-1 (TSST-1), the toxin responsible for the majority of cases of TSS. Eleven strains produced enterotoxin B, the only enterotoxin implicated in TSS, primarily in non-menstrual TSS. Enterotoxin A was produced by 15 strains and is commonly associated with the production of TSST-1, but has not been implicated in TSS. Seven strains produced enterotoxin D and one strain produced enterotoxin C, but these have not been implicated in TSS. Only 9 women used tampons which may be a major reason for the lack of menstrual TSS in Brazil, Only two of the 49 women whose sera were examined for the presence of antibodies to TSST-1 had no or very low antibody titers, the major protection against the development of TSS, both menstrual and non-menstrual TSS. This is a lower percentage than has been observed in the developed countries. Although another possibility for the lack of TSS in Brazil is the failure to recognize the disease, however, the results of this limited study indicate the importance of low usage of tampons and the high percentage of individuals with antibodies to TSST-1. The socioeconomic backgrounds of the participants were of little significance.
Keywords: Antibodies; Staphylococci; Tampons; Toxic shock syndrome; TSST-1; staphylococci; Staphylococcus aureus